1995
DOI: 10.1002/hup.470100302
|View full text |Cite
|
Sign up to set email alerts
|

Org 3770 versus amitriptyline: A 6‐week randomized double‐blind multicentre trial in hospitalized depressed patients

Abstract: Following a placebo washout period of 3-7 days, 251 hospitalized patients with a major depressive episode (DSM I11 and RDC criteria) were treated with either Org 3770 (20-60 mg/day) or amitnptyline (75-225 mg/day) for six consecutive weeks in this randomized, double-blind, multicentre study. Forty-one patients (19 Org 3770,22 amitriptyline) withdrew before completion of the 6-week active treatment period. In both groups, the main reason for withdrawal was lack of efficacy. However, fewer patients in the Org 37… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
2
2

Year Published

1996
1996
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 18 publications
(9 reference statements)
2
35
2
2
Order By: Relevance
“…Such a difference has not been reported in previous studies (Smith et al 1990;Claghorn and Lesem 1995;Marttila et al 1995;Richou et al 1995;Van Moffaert et al 1995;Zivkov and De Jong 1995). A possible explanation may be found in differences between the present and other trials with mirtazapine.…”
Section: Discussioncontrasting
confidence: 70%
See 3 more Smart Citations
“…Such a difference has not been reported in previous studies (Smith et al 1990;Claghorn and Lesem 1995;Marttila et al 1995;Richou et al 1995;Van Moffaert et al 1995;Zivkov and De Jong 1995). A possible explanation may be found in differences between the present and other trials with mirtazapine.…”
Section: Discussioncontrasting
confidence: 70%
“…Previous studies on mirtazapine (Smith et al 1990;Claghorn and Lesem 1995;Marttila et al 1995;Richou et al 1995;Van Moffaert et al 1995;Zivkov and De Jong 1995) used a flexible dose design. This may lead to inappropriate dosing especially with tricyclic antidepressants because side effects preventing dose increments may occur at subtherapeutic doses / blood levels (Dawling 1982;DUAG 1990).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The starting dose recommended by the manufacturer is 30 mg daily because the prevalence of adverse effects attributable to mirtazapine's affinity for histamine receptors (somnolence and increased appetite) is less with this dose than with lower doses. Five flexible dosing trials compared the antidepressant effect of mirtazapine with amitriptyline in psychiatric practice, and this included one in 251 patients suffering endogenous depression and requiring hospital admission (Zivkov & de Jongh, 1995). A meta-analysis concluded that there was no significant difference in the reductions in depression rating scores over six weeks (Zivkov et ai, 1995).…”
Section: Mirtazapinementioning
confidence: 99%